Symposium 8: Changing Pedagogy: Does the Introduction of Networked Learning Have an Impact on Teaching? - Thornton, Mary; Jefferies, Amanda; Jones, Indra; Alltree, Jon; Leinonen, Eeva (Proceedings of the International Conference on Networked Learning, 2004)
The University of Hertfordshire’s Managed Learning Environment initiative, known as StudyNet, was developed in-house. Throughout the development, the enhancement of learning and teaching quality has remained a central tenet. However, take up has been extremely variable. This research, through questionnaire survey, sought to assess the extent of StudyNet embeddedness, the uses to which it is put and its impact on staff working practices and pedagogy. Analysis suggests that money, time and workload affect staff access and use. As a communication and information distribution resource it is well used but its impact on the enhancement of learning and teaching is, so far, fairly limited although some examples of good practice were identified.